Effects of Rosemary (Rosmarinus officinalis L.), Onion (Allium cepa L.), and their mixtures as Natural Feed Additives on Egg Quality, Hatchability, Embryonic Development, and Chicks Quality of White Leghorn - Bekele Alemu, Seyoum; Girma Abebe, Meseret; Kebede Senbeta, Ewonetu (Journal of Poultry Sciences and Avian Diseases, 2025)
The study evaluated the effects of rosemary, onion, and their mixture extracts on egg quality, fertility, hatchability, embryonic mortality, and chick quality of White Leghorn. One hundred twenty White Leghorn layers at thirty-two weeks of age were randomly allocated to four treatments, each replicated three times with ten layers and one cock per replication and managed on a deep litter system for 70 days. The treatments were T1 (control group without any addition of feed additives), T2 (water with 4 milliliters of onion extract), T3 (water with 4ml of rosemary extract), and T4 (water with 2ml of onion and 2ml of rosemary extract mixture). Seventy-two eggs were randomly taken and evaluated for egg quality parameters such as eggshell and weight, albumen quality, and egg yolk quality. Three hundred sixty eggs were incubated and evaluated for fertility, hatchability, embryonic mortality, and chick quality. Results revealed that the use of Rosemary, Onion, and their mixtures significantly (p